The Dynamics of Language: An analysis of Speech Acts in "Sour Heart" by Jenny Zhang - Muhammad, Numan; Yang, YANG (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
Jenny Zhang's, Sour Heart, debut collection of short stories, is scrutinized with particular emphasis on the author's prose style. This paper delves extensively into the intricate mechanisms of language. The purpose of this study, which is grounded in speech act theory, is to examine how the characters' use of language to accomplish various tasks influences their identities, their relationships, and the stories' central themes. This paper’s objective is to investigate the intricate ways in which speech acts influence the meaning of literary works such as Sour Heart. Moreover, the analysis has done through a meticulous examination of several narratives.